Mitral surgical redo versus transapical transcatheter mitral valve implantation. - Alina Zubarevich (Public Library of Science (PLoS), 2021)
Background Transcatheter methods have been rapidly evolving to provide an alternative less invasive therapeutic option, mainly because redo patients often present with multiple comorbidities and high operative risk. We sought to evaluate and compare our experience with transapical transcatheter mitral valve replacement (TA-TMVR) to conventional redo mitral valve replacement in patients presenting with degenerated biological mitral valve prostheses or failed valve annuloplasty. Methods and material Between March 2012 and November 2020, 74 consecutive high-risk patients underwent surgical redo mitral valve replacement (n = 33) or TA-TMVR (n = 41) at our institution. All patients presented with a history of a surgical mitral valve procedure. All transcatheter procedures were performed using the SAPIEN XT/3™ prostheses. Data collection was prospectively according to MVARC criteria. Results The mean logistic EuroSCORE-II of the whole cohort was 19.9±16.7%, and the median STS-score was 11.1±12.5%. The mean age in the SMVR group was 63.7±12.8 years and in the TMVR group 73.6±9.7 years. Patients undergoing TA-TMVR presented with significantly higher risk scores. Echocardiography at follow up showed no obstruction of the left ventricular outflow tract, no paravalvular leakage and excellent transvalvular gradients in both groups (3.9±1.2 mmHg and 4.2±0.8 mmHg in the surgical and transcatheter arm respectively). There was no difference in postoperative major adverse events between the groups with no strokes in the whole cohort. Both methods showed similar survival rates at one year and a 30-day mortality of 15.2% and 9.8% in SAVR and TMVR group, respectively. Despite using contrast dye in the transcatheter group, the rate of postoperative acute kidney failure was similar between the groups. Conclusion Despite several contraindications for surgery, we showed the non-inferiority of TA-TMVR compared to conventional surgical redo procedures in high-risk patients. With its excellent hemodynamic and similar survival rate, TA-TMVR offers a feasible alternative to the conventional surgical redo procedure in selected patients.